UNIT 24.5 Proteomic Analysis of Protein Deamidation. (3rd November 2014) - Hao, Piliang; Sze, Siu Kwan
Abstract : Deamidation of asparagines and glutamines occurs spontaneously in proteins and results in protein degradation. Deamidation of asparaginyl residues in proteins produces a mixture of asparaginyl, n‐aspartyl, and isoaspartyl residues, which has been linked to the pathology of some neurodegenerative diseases. However, accurate proteomic analysis of deamidation is challenging since it occurs quickly during conventional proteomic sample preparation, and the co‐elution of the two resulting isomeric deamidated peptides in reversed‐phase liquid chromatography (RPLC) compromises their identification and quantification using RPLC‐MS/MS. To overcome these difficulties, a novel sample preparation protocol to minimize artificial deamidation has been developed alongside an offline RP‐ERLIC‐MS/MS (reversed‐phase chromatography fractionation followed by electrostatic repulsion‐hydrophilic interaction chromatography coupled with MS/MS) strategy to separate and quantify the three deamidation products from the same peptide on a proteome‐wide scale. These protocols are detailed in this unit. © 2014 by John Wiley & Sons, Inc.